An updated overview of Juvenile systemic sclerosis in a French cohort - Léa Jacquel; Rouba Bechara; Joëlle Terzic; Anne-Cécile Rameau; Emmanuel Chatelus; Linda Rossi-Semerano; Isabelle Kone-Paut; Ulrich Meinzer; Irène Lemelle; Charlotte Rebelle; Diego Urbina; Pascal Pillet; et al. (Pediatric Rheumatology Online Journal)
Abstract Background Systemic sclerosis encompasses a range of disorders characterized by vascular and connective tissue abnormalities. Although rare in pediatrics, juvenile systemic sclerosis (jSSc) is a severe and life-threatening condition that significantly impacts children’s development. This study aimed to provide an overview of JSSc in France over the past decade. Methods Patients with disease onset before the age of 16 were included following a request for observations sent via email to member practitioners of the SOFREMIP (French pediatric Rheumatology society). Results Our study included 18 patients from 8 different French centers. While our cohort exhibited a balanced distribution between limited and diffuse subsets of the disease, we observed a higher prevalence of the diffuse subset in children above the age of 10. Skin induration was the most reported symptom, while Raynaud’s phenomenon was present in 61% of the children at initial clinical evaluation. All children tested positive for antinuclear antibodies, with anti-Scl70 being the most common specificity, even among children with limited cutaneous subsets. Interestingly, we found a high sensitivity of the ACR / EULAR criteria for diagnosing jSSc in our cohort with 83% of patients meeting these criteria, except for 3 children who presented with overlap syndromes. Despite the frequent use of corticosteroids at the onset, no deaths or renal crises were reported. Three patients received treatment with biological agents, specifically Rituximab and Tocilizumab. Conclusion JSSc is a rare but severe disease requiring rapid, specialized, and multidisciplinary care. Further studies are needed to validate proper diagnosis criteria including overlap syndromes and evaluate the use of biotherapies in children.